2020
DOI: 10.5696/2156-9614-10.25.200309
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality in Sidi Slimane, Morocco

Abstract: Background. Groundwater is an important source of drinking water for human and animal populations and therefore should be protected from pollution. The study area, Sidi Slimane, is in the western region of Morocco, which is a highly important agricultural area. Objectives. The aim of the present study was to assess the suitability of groundwater for drinking in the Sidi Slimane region. Methods. Twenty (20) samples were collected from different locations in the study area in 2015 in order to evaluate the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The Gharb region is mainly agricultural, with extensive use of chemical fertilizers and pesticides. Combined with household emissions, this poses an ongoing risk to groundwater quality [32,33].The mapping of vulnerability to pollution of the shallow aquifer in the study area identified three vulnerability classes: low vulnerability, moderate vulnerability, and high vulnerability, which deserve special attention in terms of protection. The moderate vulnerability class represents the largest area, accounting for 71.47% of the total, highlighting a predominance of moderate intrinsic vulnerability in the study region.…”
Section: Discussionmentioning
confidence: 99%
“…The Gharb region is mainly agricultural, with extensive use of chemical fertilizers and pesticides. Combined with household emissions, this poses an ongoing risk to groundwater quality [32,33].The mapping of vulnerability to pollution of the shallow aquifer in the study area identified three vulnerability classes: low vulnerability, moderate vulnerability, and high vulnerability, which deserve special attention in terms of protection. The moderate vulnerability class represents the largest area, accounting for 71.47% of the total, highlighting a predominance of moderate intrinsic vulnerability in the study region.…”
Section: Discussionmentioning
confidence: 99%
“…2). The general trend of surface water movement in the area (hydrology of this region) is towards the northwest as shown in the Map gure (1) [7].…”
Section: Study Areamentioning
confidence: 90%
“…The region also has groundwater resources at different depths which allow it to meet irrigation needs that are potentially important asset for its socio-economic development. According to the Ministry of the Interior 2015 record [7], the main ones can be listed as below: (i) the Gharb basin with an area of 390 km², with 126 Mm 3 /year of renewable resources and a relatively balanced water balance, the one of hydrogeological interest on a regional scale characterized by a signi cant recharge by precipitation water; (ii) the Maâmora basin with an area of around 4000 km² that constitutes a large reservoir of water of 134 Mm 3 /year of renewable resources; (iii) the Témara basin with a potential input of 17 Mm 3 /year, which covers an area of 350 km 2 the depths relative to the ground oscillate between 10 m in the West and 30 m in the East; (iv) the Shoul Basin that is considered a natural extension of the Maâmora Basin, which covers an area of 200 km 2 with potential contribution of 7.5 M m 3 /year and water depth varies between 20 and 60 m.…”
Section: Introductionmentioning
confidence: 99%
“…The region also has groundwater resources at different depths, which allow it to meet irrigation needs that are potentially important assets for its socio-economic development. According to the Ministry of the Interior 2015 record [8], the main ones can be listed below: (i) the Gharb basin with an area of 390 km 2 , with 126 Mm 3 /year of renewable resources and a relatively balanced water balance, the one of hydrogeological interest on a regional scale characterized by a significant recharge by precipitation water; (ii) the Maâmora basin with an area of around 4000 km 2 that constitutes a large reservoir of water of 134 Mm 3 /year of renewable resources; (iii) the Témara basin with a potential input of 17 Mm 3 /year, which covers an area of 350 km 2 the depths relative to the ground oscillate between 10 m in the West and 30 m in the East; (iv) the Shoul Basin that is considered a natural extension of the Maâmora Basin, which covers an area of 200 km 2 with potential contribution of 7.5 M m 3 /year and water depth varies between 20 and 60 m.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, safeguarding water resources from NO 3 − contamination becomes paramount, especially in arid and semi-arid regions where water resources are both scarce and heavily utilized [6,7]. Indeed, various studies have shown that excessive groundwater extraction and the application of nitrogen-based fertilizers contribute to groundwater pollution and heighten the risks to human health [8,9].…”
Section: Introductionmentioning
confidence: 99%